The effects of storytelling on primary students' Arabic vocabulary acquisition and interest - Abu Hassan, Nur Farhanah; Mamat, Arifin (International Islamic University Malaysia, 2018)
This article reports on a quasi-experimental study conducted to determine the effectiveness of storytelling in enhancing students’ Arabic vocabulary acquisition and interest in the technique. The experiment was carried out with 24 Primary 6 students over a period of one and a half weeks at a well-established madrasah in Singapore. Two instruments were used to collect data on Arabic vocabulary acquisition and student interest in storytelling, namely Wesche and Paribakht's (1996) Vocabulary Knowledge Scale and an Interest-in-Storytelling questionnaire. To address the research questions, the study used descriptive statistics, independent samples t-test and paired samples t-test. The main observations were: i) the control group obtained a higher mastery of Arabic vocabulary after the experiment was conducted, which was due to their relatively higher academic ability; ii) the two groups had unequal ability from the very onset of the study; iii) based on Cohen’s d effect size of 3.68, the storytelling technique had a tremendous effect on the treatment group's Arabic vocabulary acquisition; and (iv) students expressed a general interest in storytelling as a means of learning Arabic vocabulary where a majority (83%) liked storytelling as a method to discover new words. The study made some recommendations on how teachers can improve their practices of storytelling to increase students' learning of Arabic vocabulary.